(untitled) (Research, Society and Development, 2022)
In recent years, there has been a lot of dialogue about social transformation in Brazil through education, recording a scenario of struggle and resistance against a past marked by colonialism. The colonial heritage still affects the most vulnerable peoples of Brazilian society in an oppressive way, and it is worth emphasizing the group of women who historically and culturally were affected by patriarchy and, for this reason, were chosen as the object of study for the research, taking based on the rupture of schooling as a sequel to exclusionary colonialism, as well as decolonial pedagogy as a hope of schooling for all genders. Through the exposed context, this article addresses the denial of women’s education as a problem, since the right to schooling was broken by historical and cultural factors of male society. For this, the research aims to understand how the coloniality of power, knowledge, being and gender in Brazil impacts on education for women. As a methodology, bibliographical research was used referring to the themes of women’s education in Brazil, coloniality and decolonial pedagogy, starting from a critical analysis based on theorists who study the subject in question and the reality of the present day, which presents advances with regard to inheritance sexist and oppressive left by the colonizers, but which still begs for struggle and resistance.